Prof. Ackermann, vision-based navigation and the PG master's degree programme at HfT Stuttgart - Hahn, Michael (Geo-spatial information science, 2023)
The two topics of the article seem to have absolutely nothing to do with each other and, as can be expected in a contribution in honor and memory of Prof. Fritz Ackermann, they are linked in his person. Vision-based Navigation was the focus of the doctoral thesis written by the author, the 29th and last PhD thesis supervised by Prof. Ackermann. The International Master's Program Photogrammetry and Geoinformatics, which the author established with colleagues at Stuttgart University of Applied Sciences (HfT Stuttgart) in 1999, was a consequence of Prof. Ackermann's benevolent promotion of international knowledge transfer in teaching. Both topics are reflected in this article; they provide further splashes of color in Prof. Ackermann's oeuvre.